2015
DOI: 10.1123/iscj.2014-0064
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Coaching Success, Servant Leadership, Cohesion, Resilience and Social Behaviors

Abstract: This study examined relationships among coaching success, servant leadership, team cohesion, athlete resilience and social behaviors utilizing responses from over 300 collegiate athletes. Horn’s (2008) model of coaching effectiveness served as the basis from which variables were operationalized and concurrently measured. Bivariate correlation analysis identified significant correlations among servant leadership and coaching success, cohesion and coaching success, cohesion and servant leadership, resilience and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
1
9
0
3
Order By: Relevance
“…The present study extends the literature on coach–athlete trust relationships 7,911,31,32 in that the evaluation of coaches’ ability is a trustworthy characteristic for athletes toward coaches. Zhang and Chelladurai 25 demonstrated that the competence of the coach is an antecedent of athletes’ trust in the coach.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The present study extends the literature on coach–athlete trust relationships 7,911,31,32 in that the evaluation of coaches’ ability is a trustworthy characteristic for athletes toward coaches. Zhang and Chelladurai 25 demonstrated that the competence of the coach is an antecedent of athletes’ trust in the coach.…”
Section: Discussionsupporting
confidence: 71%
“…30 Coaches who are servant-leaders transcend self-interest, express care and concern, and act in the best interest of their athletes, thereby creating a social context in which athletes may reciprocate by trusting. [9][10][11]31 Similarly, mutual feelings in positive closeness (i.e., trust and respect) is reported in literature on the coach-athlete relationship. 7,32 Direct experiences allow athletes to observe leadership behavior and evaluate the trustworthiness of the coach.…”
Section: Coaching Competency and Trust In The Coachmentioning
confidence: 97%
See 1 more Smart Citation
“…A study by Trigueros, Aguilar-Parra, Cangas-Díaz, Fernández-Batanero, Mañas, Arias & López-Liria [2], support for autonomy positively predicted resilience, while control behaviors indirectly predicted it negatively. Similarly, a study by Gillham, Gillham, & Hansen [62] showed that athletes' resilience developed if there is social cohesion and prosocial behaviour among team members, including the trainer. Similarly a study by Lu, Lee, Chang, Chou, Hsu, Lin, & Gill [63] where they analyzed the interactions between trainer and athlete, from the perspective of the players, showed that those athletes who felt respected and involved by the trainer had greater resilience and less stress and anxiety.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, Vinson and Parker 33 argued that servant leadership demonstrated excellent potential as a framework on which Christian sports coaches could found their practice. Gillham, Gillham 34 examined the relationship between servant leadership, coach effectiveness and other social behaviours, providing rigorous evidence to suggest that athletes’ may perceive a stronger coach-athlete relationship if they consider their coach to be trustworthy, empathetic and servant-hearted. However, as these authors acknowledge, the evidence concerning the relationship between servant leadership and coach effectiveness was much less strong.…”
Section: Introductionmentioning
confidence: 99%